Childhood vasculitides in Turkey: A nationwide survey - ALPAY, HARİKA (My University, 2007)
Aim: The aims of this study were to evaluate the characteristics of childhood vasculitides and to establish the first registry in Turkey, an eastern Mediterranean country with a white population. Patients and methods: A questionnaire was distributed to the main referral centers asking for the registration of the Henoch-Schönlein purpura (HSP) patients in the last calendar year only and 5 years for other vasculitides. Demographic, clinical, and laboratory data were assessed. Results: Vasculitic diseases were registered from 15 pediatric centers. These centers had a fair representation throughout the country. In the last calendar year, incidences were as follows: HSP 81.6%, Kawasaki disease (KD) 9.0%, childhood polyarteritis nodosa (C-PAN) 5.6%, Takayasu arteritis (TA) 1.5%, Wegener's granulomatosis 0.4%, and Behçet disease 1.9%. There was no clear gender dominance. The mean age was 11.05±4.89 years. Acute phase reactants were elevated in almost all, highest figures being in C-PAN. Renal involvement was present in 28.6% of HSP and 53% of the C-PAN patients. Abdominal aorta was involved in all TA patients. Among the C-PAN patients, 25% had microscopic PAN with necrotizing glomerulonephritis; antineutrophil cytoplasmic antibody was positive in those who were studied. Among the patients, 12.5% and 15% had classic PAN and cutaneous PAN, respectively. The remaining majority were classified as systemic C-PAN diagnosed with biopsies and/or angiograms demonstrating small to midsize artery involvement. The overall prognosis was better than reported in adult series. Conclusion: This is the largest multicenter study defining the demographic data for childhood vasculitides. The distribution of childhood vasculitides was different in our population where KD is much less frequent, whereas HSP constitutes an overwhelming majority. C-PAN was more frequent as well. © Clinical Rheumatology 2006.
Keywords: Childhood; Epidemiology; Vasculitis